Prospects of development of incoming tourism from Latin America to Russia - C N. Amirgamzayeva (Ибероамериканские тетради, 2019)
Tourist flows from the Latin American countries to Russia increased significantly in 2018. This growth was mainly a result of the FIFA World Cup held in Russia and the huge interest in football in the Latin American countries, and not of a smart policy of the tourism brand promotion, infrastructure development or lowering the tours prices. However, this growth can give momentum to increasing the tourist flows in future.